Leisure-time and commuting physical activity and subsequent sickness absence among young and early midlife employees: a register-linked follow-up study 2017–2020 - Ville Päivärinne; Pi Fagerlund; Jouni Lahti; Ossi Rahkonen; Tea Lallukka (International Archives of Occupational and Environmental Health, 2026)
Abstract Purpose We examined leisure-time physical activity (LTPA) and active commuting (AC) and their associations with subsequent sickness absence (SA) among young and early midlife employees. Methods The 2017 Helsinki Health Study survey among employees of the City of Helsinki aged 19–39 was prospectively linked to register-based data on total, short- and long-term SA spells (2017–2020). LTPA (n=3618) and AC (n=3513) were assessed as weekly metabolic equivalent (MET) hours in 2017. LTPA was categorized into five groups based on intensity and weekly volume (inactivity, moderate, moderate-to-vigorous, vigorous and high vigorous) and AC into four groups (inactive, low moderate, moderate-to-vigorous, vigorous). Analyses were stratified by sex and adjusted for sociodemographic and lifestyle factors using negative binomial regression to estimate incidence rate ratios (IRRs) and their 95% confidence intervals (CIs). Results Women had more SA than men (135 vs 97 days per 10 person-years; p